'No magic number' means 'no magic number': will the EU Court turn the tide on four-to-three mobile mergers in Europe?. Issue 2 (August 2021) - Czapracka, Katarzyna
Abstract : This article explores the impact of the General Court's judgment in CK Telecoms and the Commission decision in T-Mobile NL/Tele2 on the assessment of four-to-three mobile mergers. The unconditional clearance in the Dutch case energized some telecoms executives, but the Commission stressed that it was largely due to the very specific circumstances of the case. Then, in CK Telecoms, the General Court delivered a blow to the framework developed by the Commission to assess mobile mergers. The Court's interpretation of the concepts of 'important competitive force' and 'closeness of competition' raises the threshold for the Commission to challenge mergers and implements the principle that there is no 'magic number' of mobile network operators. Though some commentators compared CK Telecoms to the Airtours case, CK Telecoms has not provoked similar soul-searching at DG Competition. Some senior Commission officials criticized the judgment and indicated that the Commission will continue applying the same framework. On appeal, the Commission has challenged all key aspects of the judgment. The Dutch case, however, confirms that the Commission may entertain unconditional clearance in some four-to-three mobile mergers and, while CK Telecoms might not bring an overhaul of the current framework, we can expect some refinements.